The implementation of School-Based Assessment System in Malaysia: a study of teacher perceptions - Nor Hasnida Che Md Ghazali (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
The school-based assessment system is a holistic assessment system conducted in school by subject teachers to assess the students’ cognitive (intellect), affective (emotional and spiritual) and psychomotor (physical) aspects in line with Malaysia’s National Philosophy of Education and the Standards-based School Curriculum. This study evaluated the implementation of SBA in Malaysian schools in the course of preparing a summative report on the effectiveness of the system. The model proposed examined the interrelationship between the evaluation dimensions (input, process and product). It was hypothesized that process would be positively associated with product, and input with both process and product. Although SBA is still in its infancy it is becoming increasingly important that it be evaluated considering its impact on students’ achievement in an upper middle-income developing country like Malaysia. The study took nearly two years. A self-administered questionnaire was designed based on the Daniel Stufflebeam CIPP (context-input-process-product) evaluation format. The primary data were derived from a total of 776 primary and secondary school teachers who have been sampled using a stratified random sampling of schools. The results revealed a reasonable fit with the SBA evaluation model with an interrelationship between the three dimensions of evaluation (input, process and product). Theoretical, methodological and practical implications suggested the importance of the findings to different audiences.